A modified, optimized kinetic photometric thrombin generation assay components to measure the potency of thrombin in plasma - Zrari, Salar A. (Cellular and Molecular Biology, 2022)
The purpose of the present study was to improve, optimize and modification, a kinetic photometric assay of Factor IIa activity with regard to blood sample types, calibration, analytic corrections, and activation reagents, in order to establish a rapid routine, less time consuming, and suitable method for the evaluation of large numbers of clinical samples. Our modified method was based on the continuous monitoring of the Factor IIa released from the reacting substance, in the presence of a specific chromogenic peptide substrate (S2238). The optimization of pH and of the concentrations of substrate, activator (CaCl2), EDTA, and tissue factor was carried out as well as blood sample types (Platelet-rich and platelet-poor plasma samples) so as to ensure the best compromise between reliability, specificity, and sensitivity, However, the Factor IIa activity was compared in the plasma of different donors. In conclusion, our modified and optimized FIIa generation assay is a rapid and simple method for the diagnosis and monitoring of different clinical cases, at the same time it can be easily adapted to clinical chemistry analyzers.